Analisis Perizinan pendaftaran Persekutuan Firma dan Komanditer dalam Berbisnis - Hafiz Arrizal, Brian (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Indonesia is a country that is very rich in natural resources and in national development the economy is a very important factor for a country, the bigger the economy in a country, the country will be a strong country, one of the supporting factors for the economy in a country is the number of business actors in a country, the more business actors, the faster and greater the economic growth in that country, in doing business it is not necessarily done alone, in the business world we can establish cooperation with other parties, for example, a partnership of firms. A Firm Partnership is a cooperative activity that is commonly carried out in the business world, in a short sense it can be said that two companies or several companies join and establish cooperation to achieve a common goal. All regulations governing a firm partnership are contained in the regulations of the minister of law and human rights Republik Indonesia No 17 of 2018 concerning registration of limited partnerships, firm partnerships, and civil partnerships and the Commercial Code or Criminal Code. In the two sources of law, it is explained in detail regarding the partnership of firms, however, there are slight differences between the two sources of law, so that there are several sources of law that must take precedence over other sources of law in accordance with the hierarchy of laws in Indonesia. In the process of licensing and establishment, an association requires an authentic deed as a condition for its establishment, because an authentic deed is a symbol of a company. In the process of amending the articles of association, various stages must be passed, from an application to the business entity administration system or SABU to several things that must be completed. And in the process of dissolving the firm partnership, it has been explained in the book of commercial law articles 16 – 35. In this discussion, the aim is to better understand the process of obtaining firm licensing up to firm licensing. The results of this study are how a firm partnership can occur, the legal basis for the implementation and dissolution of a firm partnership